2014
DOI: 10.1891/1933-3196.8.3.103
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movement Desensitization and Reprocessing as an Adjunctive Treatment of Unipolar Depression: A Controlled Study

Abstract: Depression is a severe mental disorder that challenges mental health systems worldwide. About 30% of treated patients do not experience a full remission after treatment, and more than 75% of patients suffer from recurrent depressive episodes. Although psychotherapy and medication can improve remission rates, the success rates of current treatments are limited. In this nonrandomized controlled exploratory study, 21 patients with unipolar primary depression were treated with a mean of 44.5 sessions of Cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 38 publications
1
26
0
2
Order By: Relevance
“…The Hofmann study used EMDR sessions (between 3 and 16) as an adjunct to CBT (around 38 sessions), with the CBT+EMDR group achieving significantly greater improvements in depression symptoms than those receiving CBT alone. By using only standard protocol EMDR, this study appears to have seen results equivalent to the German study but in half the number of sessions (20 instead of 40-50 sessions; Hofmann et al, 2014).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The Hofmann study used EMDR sessions (between 3 and 16) as an adjunct to CBT (around 38 sessions), with the CBT+EMDR group achieving significantly greater improvements in depression symptoms than those receiving CBT alone. By using only standard protocol EMDR, this study appears to have seen results equivalent to the German study but in half the number of sessions (20 instead of 40-50 sessions; Hofmann et al, 2014).…”
Section: Discussionmentioning
confidence: 58%
“…This study adds to a small, but growing body of literature that indicates EMDR has potential to treat depression (Bae et al, 2008;Grey, 2011;Hofmann et al, 2014) and symptoms of depression and hypomania in bipolar patients (Novo et al, 2014). It also shows that EMDR does not necessarily need to be an adjunct to another therapy but can be used as the standard protocol describes (Shapiro, 2001).…”
Section: Discussionmentioning
confidence: 85%
“…The original list of traumatic events covering medical trauma, natural disasters, community violence and abuse was adapted for the present study by adding four items concerning experiences of loss and separation (death and separation from loved ones) and humiliation (bullying and being isolated/ignored). These experiences, considered as 'attachment trauma' (Hofmann et al, 2014) have been identified as being connected to the onset of depressive episodes (see, e.g., Bae et al, 2008;Kendler et al, 2003). Reliability of the UCLA total scale in the current study was excellent (α = .91).…”
Section: Assessment Instrumentsmentioning
confidence: 53%
“…In the past 5 years, several studies have been conducted demonstrating preliminary evidence for the efficacy of EMDR therapy in the treatment of MDD in adults. Promising results were obtained from studies investigating EMDR therapy as an adjacent therapy to CBT (Hofmann et al, 2014), to pharmacological treatment (Minelli et al, 2019;Ostacoli et al, 2018) and to inpatient treatment (Hase et al, 2015(Hase et al, , 2018. Three studies, investigating the efficacy of EMDR as a stand-alone treatment, demonstrated significant reductions of depressive symptoms (Gauhar, 2016), even for patients with long-term depression (Wood, Ricketts, & Parry, 2018) and treatment-resistant depression (Minelli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent randomized controlled trial, EMDR was used as an adjunctive therapy to CBT for treating depression. EMDR sessions added to a course of CBT showed additional therapeutic gains [43]. That study used the standard EMDR protocol as well.…”
Section: Evolutionary Theory In Treating Depressionmentioning
confidence: 98%